Indirect rule? Marriage, polygamy, and the endurance of British Methodist Theology in a post-colonial world - Morris-Chapman, Daniel Pratt (Stellenbosch theological journal, 2022)
During the post-War period, British Methodist commentators have sought to portray their denomination in a favourable light by highlighting the manner in which this Church supported movements toward ecclesial autonomy in their former British colonies. This narrative, which at times attempts to contrast British Methodism with the United Methodist Church, holds that the "Methodist Church in Britain is not identical in ethos" to Methodism in "the United States," which has struggled to retain a global presence (Beck 2002:106). However, while this may be so, it is evident that British Methodism has also continued to exert considerable influence in its former overseas districts which, after obtaining independence, have generally continued to retain the doctrinal standards that they inherited from the founding denomination. Taking the Methodist Church in Zimbabwe as an example, this essay explores the way in which these continue to exert a negative influence on the lives of many Christian people today.